Enhanced disappearance of mesotrione and fomesafen by water hyacinth (Eichhornia crassipes) in water. Issue 6 (12th May 2019) - Chen, Zhaojie; Huang, Lulu; Song, Shiming; Zhang, Yan; Li, Yuanfu; Tan, Huihua; Li, Xuesheng
Abstract: This study aimed to investigate the potential use of water hyacinth ( Eichhornia crassipes ) in removing two herbicides (mesotrione and fomesafen) with long degradation cycles in water. The relative growth rate (RGR) of water hyacinth in the presence of 100-mg/L mesotrione and fomesafen was significantly lower than that in their absence, particularly with fomesafen. Moreover, the RGRFW and RGRDW with treatment with fomesafen were 1.47- and 1.58-fold lower than those with treatment with mesotrione, respectively. The disappearance rate constants of mesotrione and fomesafen in natural water were, respectively, 0.1148 and 0.0276 d −1 with plants and 0.0038 and 0.0005 d −1 without plants. The disappearance rate constants with and without plants were significantly different, indicating that uptake by plants combined with degradation by plant-associated bacteria account for 96.7% and 98.2% of the removal of mesotrione and fomesafen, respectively. The bioconcentration factor for mesotrione and fomesafen in living water hyacinth plants ranged 0.38–16.97 and 1.05–3.50 L/kg, respectively, whereas the residues of mesotrione and fomesafen in water decreased by 70–92 and 22–34%, respectively, after the plants were grown for 14 d in culture solution with 100-mg/L mesotrione and fomesafen. These results show that uptake by plants combined with degradation by plant-associated bacteria may be the dominant process in the removal of mesotrione and fomesafen from water by plants. Water hyacinth may be applied as an efficient, economical, and ecological alternative to accelerate the removal and degradation of agro-industrial waste water polluted with mesotrione and fomesafen.